ANALISIS STRATEGI BISNIS PADA UD. BRONTOSENO - Susilowati, Susilowati; Hapsari, Raditha Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to identify and set the appropriate business strategy for UD. Brontoseno. This descriptive study was designed to collect data explaining the characteristics of people, events, or situations. The data was collected through documentation, library research, observations, and direct interviews with the company’s owner, employees, and customers. The methods of analysis are EFAS and IFAS, SWOT matrix, SWOT Choosing, IE (Internal-External) matrix, and QSPM. This study finds that hold and maintain is the most appropriate strategy for UD. Brontoseno and that aggressive strategy can strengthen the hold and maintain strategy.